Association of Heme Oxygenase 1 with Lung Protection in Malaria-Associated ALI/ARDS - Marcelo L. M. Pereira; Luana S. Ortolan; Michelle K. Sercundes; Daniela Debone; Oscar Murillo; Flávia A. Lima; Claudio R. F. Marinho; Sabrina Epiphanio (Mediators of Inflammation)
Malaria is a serious disease, caused by the parasite of the genus Plasmodium, which was responsible for 440,000 deaths in 2015. Acute lung injury/acute respiratory distress syndrome (ALI/ARDS) is one of the main clinical complications in severe malaria. The murine model DBA/2 reproduces the clinical signs of ALI/ARDS in humans, when infected with Plasmodium berghei ANKA. High levels of HO-1 were reported in cases of severe malaria. Our data indicated that the HO-1 mRNA and protein expression are increased in mice that develop malaria-associated ALI/ARDS (MA-ALI/ARDS). Additionally, the hemin, a HO-1 inducing drug, prevented mice from developing MA-ALI/ARDS when administered prior to the development of MA-ALI/ARDS in this model. Also, hemin treatment showed an amelioration of respiratory parameters in mice, high VEGF levels in the sera, and a decrease in vascular permeability in the lung, which are signs of ALI/ARDS. Therefore, the induction of HO-1 before the development of MA-ALI/ARDS could be protective. However, the increased expression of HO-1 on the onset of MA-ALI/ARDS development may represent an effort to revert the phenotype of this syndrome by the host. We therefore confirm that HO-1 inducing drugs could be used for prevention of MA-ALI/ARDS in humans.